ANALISIS DAMPAK EKONOMI DAN SOSIAL AKTIVITAS PT. WALETINDO SETIA PERSADA BAGI MASYARAKAT DESA SINDANG MARGA - Muhammad Chalifatul Mu’minin Assidqie; Erwin Saputra Siregar; Dessy Anggraini (CV. Aksara Global Akademia, 2024)
Coal is one of the energy sources in the world. Coal is a very complex mixture of organic chemicals containing carbon, oxygen and hydrogen in a carbon chain. Sindang Marga Village is one of the villages in Bayung Lencir sub-district, Musi Banyuasin Regency, South Sumatra province. Based on survey data, it is known that the number of people in the village is 1,700 people, including those who do not yet have identity cards. After the establishment of a mining company, it is hoped that it will be able to raise the level of socio-economic conditions for the people of Sindang Marga village, both those without families and those with families. If people's income increases, of course the level of community welfare will also improve. The aim of this research was to determine the economic and social impact on society of PT activities. Waletindo Setia Persada in Sindang Marga Village, Bayung Lencir District, Musi Banyuasin Regency. This research is field research with a qualitative type of research. Data collection techniques use observation, interviews and documentation. The data analysis technique used is qualitative descriptive analysis, which consists of three activity streams, namely data reduction, data presentation and drawing conclusions. The research results show that the impact resulting from the activities of PT. Waletindo Setia Persada in Sindang Marga Village is a change in the livelihoods of the people of Sindang Marga Village from the agricultural sector to the mining sector, increasing micro businesses and minimizing unemployment. The existence of the Company also causes an increase in income and changes people's standard of living for the better. There are changes in behavior patterns in society, both positive and negative, such as income disparities, disruption of public roads, health problems and conflict.